Pengenalan dan Penggunaan PPT Interaktif Dalam Proses Pembelajaran Fisika di Sekolah - Putri Gifari; Irman Muliadi; Gunawan Gunawan (Indonesian Journal of Education and Community Services, 2026)
The use of technology-based learning media has become essential in 21st-century education, particularly in physics learning, which requires mastery of abstract concepts. This study aims to describe the effectiveness of introducing and implementing interactive PowerPoint in enhancing student engagement, conceptual understanding, and learning outcomes. A quasi-experimental pretest–posttest design was used with 36 tenth-grade students. Research instruments included concept mastery tests, learning activity observation sheets, and student response questionnaires. The results indicate an increase in average learning scores from 62.5 to 83.4, with an N-Gain of 0.56 (moderate category). Student activity increased from 58% to 86% (very active category). Most students (93.75%) responded positively to the interactive PPT, particularly to its physics simulation animations and interactive navigation buttons. Therefore, interactive PowerPoint is proven effective in improving the quality of physics learning and is highly recommended for broader implementation.